CRITICISM OF HADITH AUTHENTICITY ON CONTEMPORARY ISLAMIC THINKERS - Hafid, Erwin; Mahmuddin, Mahmuddin (Journal of Islam and Science, 2022)
Islam knows two primary sources in its legislation, first, the holy Qur’an and the second, Hadith, however, there is a significant difference in the inventory system of both sources. This study aims to discuss about how are the modern Islamic scholars’ perspectives on the Hadith authenticity. The method used is qualitative. Qualitative methods are used to examine natural objects, where researchers become key instruments. In addition, data collected are triangulated (combined), data analyses are inductive, and the results of qualitative research emphasize meaning rather than generalization. The interaction of moslems with the Prophet’s Hadith is very dynamic. The attention of it was not very big at the beginning of Islam because the Prophet was still alive and lived around them at that time as the living Islam (the source of everything), but in the period after the Prophet’s death, the attention to the Hadith increased rapidly. The contemporary Islamic thinkers assume that the Hadith scholars have not given great attention to matan criticism as what in sanad has. The critic opportunity is still opened on the Prophet’s authenticity by using internal criticism (matan of Hadith), as long as using the right methodology as the Hadith scholars have explained.